Italian Presence in the Albanian Economy Between First and Second World War - Pacukaj, Sokol (Mediterranean Journal of Social Sciences, 2012)
Italy and Albania are two countries that were forced from their geographical proximity, are condemned continue tohave economic relations and social policies that date back to the Albanian diaspora led by Giorgio Castriota in Calabria at theend of 1400 with Italy forced to play against the Albanian people and the role of the elder brother of the sheriff reluctant. Theobjective of this paper is to reconstruct the main events of the economic history of Albania in the period after independence,which was characterized by progressive expansion in the field Economic, financial and political hegemony of the Italian in thetwenty years between the first postwar annexation in 1939, Albania to Italy. As we will see the 'spread of Italian influence willoccur in stages, before redirecting the Albanian foreign trade to Italy, then extending to the financial sector with theestablishment of central bank Albanian, then to grow in mining, agriculture and industry with the establishment of Italian andItalian Albanian companies in albanian territory.